MICROHARDNESS OF CERAMIC MATERIALS BASED ON Ge-DOPED ARGYRODITE Ag6PS5I - Filep, Michael; Pogodin, Artem; Shender, Iryna; Malakhovska, Tetyana; Bilanych, Vitaliy; Kokhan, Oleksandr (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2023)
This paper presents the preparation of microcrystalline powders of Ag6PS5I, solid solutions of Ag6+xP1-xGexS5I (x = 0.25, 0.5, 0.75) and ceramic materials based on them. The microhardness of the ceramic samples was measured and the effect of heterovalent substitution of P5+↔Ge4+ on the mechanical properties of the studied samples was determined. The synthesis of initial Ag6PS5I and necessary for doping Ag7GeS5I was performed from the high purity elemental components (Ag, P, Ge, S) and previously synthesized binary AgI. Solid solutions of the Ag6+xP1-xGexS5I (x = 0.25, 0.5, 0.75) composition were synthesized from previously synthesised Ag6PS5I and Ag7GeS5I taken in stoichiometric amounts by a direct one-temperature method. As a result, polycrystalline bulk alloys of Ag6+xP1-xGexS5I solid were obtained. Microcrystalline Ag6+xP1-xGexS5I powders were obtained from the synthesized polycrystalline alloys by mechanical grinding (agate mortar). The powders were sieved through sieves with a pore size of 20 μm and 10 μm to obtain a fraction of crystallites with a size of 10-20 μm. The phase composition of the obtained powders was studied by means of XRD method. It has been found that the powder patterns of the studied samples are characterized by the presence only of one system of reflexes corresponding to the face-centred cubic cell with SG F-43m. The resulting micropowders were pressed (P ~ 400 MPa) in the form of discs and annealed at 650 °С in vacuum quartz ampoules. The microhardness of the ceramics obtained in this way was measured by the Vickers method. For all ceramics, a decrease in the microhardness H is observed with an increase in the load P. This indicates that a direct size effect is observed for ceramics made on the basis of solid solutions of Ag6+xP1-xGexS5I. The obtained values of microhardness at a load of P > 1–1.5 N are independent of the load, which indicates the achievement of intrinsic hardness. Meyer's law was used to further analyze the microhardness and size effect of Ag6+xP1-xGexS5I solid solutions. The obtained values of the Meyer's index for Ag6+xP1-xGexS5I based ceramics are in the range n = 1.78 ÷ 1.81, which demonstrates the implementation of a direct size effect in these samples and indicates that the studied ceramics belong to soft materials. The concentration dependence of the microhardness indicates that an increase in the Germanium content in ceramic materials of solid solutions of Ag6+xP1-xGexS5I leads to a decrease in the microhardness of the materials.